(3PNGFQ GdYbHj hefGbH Phi GdbQHis - (3eMH GdOjf GdWHQj , CMeO Hf YHO Gddg Hf eMeO TjN GdMQe, eMH GdOjf CHh GdYHGS,J (B694 (3g` s ((3Ydi Hf MSH Gddg GdYRj GdYLdGfj s)
(3ChdgG (B:s
(3CeG HYO , aEf Gddg YR hLd EUWai eMeOkG Udi Gddg Ydjg hSde Ydi LejY ef ShGg s
(3BNQgG (B:s
(3bGd CHhHcQ dYeQ QVi Gddg YfgeG(B: (3GfWdb HfG Edi Ce Cjef hjbGd EfgG GdJi TQHJ Hhdg Udi Gddg Ydjg hSde s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B159 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B298s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B361 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B615 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B182 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs